Online Access to Advertising Films and TV-Commercials - Stenalt, Maria Hvid (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The audiovisual cultural heritage is a valuable collection that both reflects contemporary developments in the 20th century and at the same time is a source material for research. The purpose of this paper is to describe how the State and University Library established a digital archive for Danish film and TV-commercials, why the collection is important, and how it became available online to students and researchers. The process presents a number of challenges including copyright and technical issues. The scalable and integrated service may be used for other audiovisual collections in the future.